Underwriting Cycles and Crises - Piotr Manikowski (Мир новой экономики, 2018)
The cyclicality of underwriting profits for the property-liability insurance industry has been extensively researched. The underwriting cycle refers to a repeating series of phases that insurance markets go through. The sequence of hard and soft markets may be observed in prices, profitability, and supply (capacity) for insurance. In this study we try to describe in detail phases of insurance cycles and its characteristics. We put a special emphasis into crises (hard markets). We also present some historical data about crises, its causes and consequence on the example of the US insurance market.